Recalibration versus laminectomy for lumbar decompression in patients over 50 years of age: evaluation using the Oswestry Disability Scale - García, Juan Pablo; Sanchez Ceron, José Mauro Esteban (Revista Argentina de Neurocirugía, 2024)
Background. Lumbar spinal stenosis is the most common spinal condition in elderly patients, with an incidence of 1,7 to 8%. Objectives. To evaluate which surgical technique between lumbar recalibration and laminectomy has the best result for patients over 50 years old with lumbar stenosis, using the Oswestry low back pain disability scale.Methods. Observational, retrospective and cross-sectional study. The sample was formed by patients who had lumbar stenosis and underwent lumbar recalibration surgery or laminectomy between January 1st 2015 and December 31st 2020.Results. Patients who underwent laminectomy (85.7%) progressed to minimal functional limitation and 14,3% to moderate functional limitation. Of the patients who underwent recalibration, 64% progressed to minimal functional limitation, 29,5% to moderate, and 6,5% to severe.Conclusion. The laminectomy procedure is associated with better outcomes; this may be because it allows better visualization of the dura mater in patients with moderate to severe narrow ducts. The removal of the yellow ligament in its central portion and towards the lateral recesses is more comfortable and effective in decompressing the nerve root of the segment, allowing access to the neuroforamen for its enlargement.
Keywords: Laminectomy; Lumbar; Neurosurgery; Stenosis